1) (a²+2ab+b²)(a-b)-2ab²+2a²b-6a²b+6ab²=(a-b)³
a³-a²b+2a²b-2ab²+ab²-b³-2ab²+2a²b-6a²b+6ab²= (a-b)³
a³-3a²b+3ab²-b³=(a-b)³
(a-b)³=(a-b)³
2) a^6+b^6+a^6-b^6=2a^6
2a^6=2a^6
3) a²c²+b²c²+a²d²+b²d²= a²c²+2abcd+b²c²+a²d²-2abcd+b²d²
a²c²+b²c²+a²d²+b²d²=a²c²+b²c²+a²d²+b²d²
4) a²d²+a²ce²+b²cd²+b²c²e²= a²d²+2abcde+b²c²e²+a²ce²-2abcde+b²cd²
a²d²+a²ce²+b²cd²+b²c²e²= a²d²+b²c²e²+a²ce²+b²cd²
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
1) (a²+2ab+b²)(a-b)-2ab²+2a²b-6a²b+6ab²=(a-b)³
a³-a²b+2a²b-2ab²+ab²-b³-2ab²+2a²b-6a²b+6ab²= (a-b)³
a³-3a²b+3ab²-b³=(a-b)³
(a-b)³=(a-b)³
2) a^6+b^6+a^6-b^6=2a^6
2a^6=2a^6
3) a²c²+b²c²+a²d²+b²d²= a²c²+2abcd+b²c²+a²d²-2abcd+b²d²
a²c²+b²c²+a²d²+b²d²=a²c²+b²c²+a²d²+b²d²
4) a²d²+a²ce²+b²cd²+b²c²e²= a²d²+2abcde+b²c²e²+a²ce²-2abcde+b²cd²
a²d²+a²ce²+b²cd²+b²c²e²= a²d²+b²c²e²+a²ce²+b²cd²